Identifikasi Jenis Selaginela Sp di Universitas Pendidikan Muhammadiyah (Unimuda) Sorong - Mayor, Agnes Sarlota; Prabawati, Ratna; Hidayatussakinah, Hidayatussakinah (STKIP HARAPAN BIMA, 2026)
This study aimed to identify and describe the morphological characteristics of Selaginella species growing in the environment of Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong. The research employed a descriptive qualitative approach conducted from March 17 to March 25, 2025, at several locations, namely the Rusunawa Building, Rectorate Building, and Khalid Bin Walid Field. The research objects included all Selaginella specimens found at the study sites. Data were collected through field surveys, direct observations, and documentation of morphological characteristics, including roots, stems, microphyll leaves, and sporophylls. Species identification was carried out by comparing observational findings with scientific literature, flora references, and plant identification key applications. Data analysis was conducted descriptively using a qualitative approach by classifying and explaining the observed morphological traits. The results revealed two species, namely Selaginella willdenowii, found in moist and shaded areas near the Rusunawa Building, and Selaginella kraussiana, growing on moist soils around the Rectorate Building and Khalid Bin Walid Field. The presence of these species indicates that the campus microclimate supports the growth of the genus Selaginella and has potential as a learning resource for fern plant biodiversity